Pregnancy in women with sickle cell anemia: an integrative review - Santana, Joseany da Silva; Lima da Silva, Jorge Luiz; Mello, Gabriel de Moura; Bortolazzo, Pedro Antonio Alves Bezerra; Bento, Luiz Carlos dos Santos; Souza, Angelica Boaventura de (Journal of Health Care, 2017)
Objective: To analyze Brazilian scientific productions about gestation in patients with sickle cell anemia. Method: It is an integrative review study carried out in the Virtual Health Library (VHL) database, using the descriptors pregnancy and sickle cell anemia, in the periodical from 2006 to 2015. Results: The publications focused on the Southeast region of Brazil, where the number of cases is lower than in other regions. The complicating gestational factors in sickle cell anemia were anemia, infections, preterm labor, teenage pregnancy, among others. And factors that increased maternal and fetal risks were spontaneous abortion, early rupture of membranes, restricted intrauterine growth, postpartum infection, among others. Conclusion: It is necessary that the pregnant women with sickle cell anemia be accompanied by a multiprofessional reference group in high risk pregnancy, the hematologist and the primary health care team aiming at integral care and the reduction and / or control of maternal and fetal risks.
Keywords: Nursing; Risk factors; Anemia; Sickle Cell; Pregnancy